Salivary gland secretome: a novel tool towards molecular stratification of patients with primary Sjögren’s syndrome and non-autoimmune sicca - Timothy R D J Radstake; Joel A G van Roon; Maarten R Hillen; Sofie L M Blokland; Aike A Kruize; Fréderique M van Vliet-Moret; Angela Bikker; Wilco de Jager; Aridaman Pandit (RMD Open)
Objective To explore the potential of salivary gland biopsy supernatants (the secretome) as a novel tool to aid in stratification of patients with sicca syndrome and to study local immunopathology in Sjögren’s syndrome.Methods Labial salivary gland biopsies were incubated in saline for 1 hour. In these tissue supernatants from a discovery cohort (n=16) of patients with primary Sjögren’s syndrome (pSS) and non-Sjögren’s sicca (nSS), 101 inflammatory mediators were measured by Luminex. Results were validated in a replication cohort (n=57) encompassing patients with pSS, incomplete SS and nSS.Results The levels of 23 cytokines were significantly increased in patients with pSS versus nSS in the discovery cohort. These 23 and 3 additional cytokines were measured in a second cohort. Elevated concentrations of 11 cytokines were validated and the majority correlated with clinical parameters. Classification tree analysis indicated that the concentrations of CXCL13, IL-21, sIL-2R and sIL-7Rα could be used to classify 95.8% of patients with pSS correctly.Conclusion Labial salivary gland secretomes can be used to reliably assess mediators involved in immunopathology of patients with pSS, potentially contributing to patient classification. As such, this method represents a novel tool to identify therapeutic targets and markers for diagnosis, prognosis and treatment response.